Determinan Pemanfaatan Pos Kesehatan Desa (POSKESDES) Pada Keluarga Di Desa Keude Lueng Putu Kecamatan Bandar Baru Kabupaten Pidie Jaya - Nadhya Hidayatul Ulfa; Asriwati Asriwati; Yuniati Yuniati; Indah Anggraini; Tri Niswati Utami (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2023)
Village Health Posts (Poskesdes) are community-based health efforts (UKBM) established in villages in order to bring/provide basic health services for rural communities. Activities carried out include promotive, preventive, and curative activities including monitoring of nutritional status, as well as the health of pregnant women, disease management, preparedness and disaster management. The purpose of the study was to determine the determinants of the use of Village Health Posts (Poskesdes) in families in Keude Lueng Putu Village, Bandar Baru District, Pidie Jaya Regency. The research design used a quantitative method which was carried out by an analytical survey with a Cross Sectional Study approach. The population in this study was the entire community as many as 1,132 housewives. The sample used the purposive sampling technique of 91 housewives. Data analysis used univariate, bivariate and multivariate analysis. The results showed that there was an influence of knowledge p = 0.027, family support p = 0.004 and distance p = 0.037 variables that did not have a relationship, namely the attitude and support of health workers on the use of Village Health Posts (Poskesdes) in families in Keude Lueng Putu Village, Bandar Baru District. Pidie Jaya Regency. While the most dominant factor is family support p = 0.001, 95% CI = 2.655-39,141 with OR = 10,195. The conclusion of this study is that there is an influence of knowledge, family support and distance while the most dominant factor is family support for the use of Village Health Posts (Poskesdes) in families in Keude Lueng Putu Village, Bandar Baru District, Pidie Jaya Regency. It is recommended to Poskesdes officers to provide information and provide counseling to families in order to increase family knowledge so as to support other family members to take advantage of Poskesdes.